2016
DOI: 10.1161/strokeaha.116.013929
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Device Choice on the Effect of Intra-Arterial Treatment for Acute Ischemic Stroke in MR CLEAN (Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands)

Abstract: Background and Purpose— Intra-arterial treatment by means of retrievable stents has been proven safe and effective. In MR CLEAN (Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands), the choice of the type of thrombectomy device was left to the discretion of the interventionist. The aim of this study was to explore the differences in functional outcome, neurological recovery, reperfusion, extent of infarction, and adverse events according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The recanalization rates and 90 day mRS scores are similar among the studies presented in table 3. This observation supports the assertion that thrombectomy with self-expanding stent-like devices is a valid treatment for AIS and that similar clinical and angiographic results can be obtained using different types of stentriever devices 32 33. We are unable to draw firm conclusions on this observation because we do not have a control group.…”
Section: Discussionsupporting
confidence: 79%
“…The recanalization rates and 90 day mRS scores are similar among the studies presented in table 3. This observation supports the assertion that thrombectomy with self-expanding stent-like devices is a valid treatment for AIS and that similar clinical and angiographic results can be obtained using different types of stentriever devices 32 33. We are unable to draw firm conclusions on this observation because we do not have a control group.…”
Section: Discussionsupporting
confidence: 79%
“…Treatment method had no impact on outcomes in this trial. 179 In THRACE, an intra-arterial lytic was used to a maximum dose of 0.3 mg/kg and allowed to establish goal reperfusion, only after mechanical thrombectomy was attempted. A mean dose of 8.8 mg was administered in 15 of 141 patients receiving mechanical thrombectomy (11%).…”
Section: B-rmentioning
confidence: 99%
“…[ 16 ] But, there are few direct comparison studies of the 2 widely used stents, the Solitaire and the Trevo, one small series and a systematic review with a meta-analysis have been published previously. [ 2 , 14 , 17 ] And they reported that there was no significant difference in recanalization rates or functional outcome between the 2 stents. So, the purpose of this study was to directly compare clinical and radiologic outcomes, multiple time intervals, and safety variables of 2 widely used stent retriever devices (Solitaire, Trevo).…”
Section: Discussionmentioning
confidence: 99%